Improving the Knowledge of Migrant Workers' Children in Managing Finances with Rupiah Currency - Roisah Roisah; Siti Nur Azizah (Universitas Muhammadiyah Purwokerto, 2025)
This study aims to enhance the financial literacy of children of Indonesian migrant workers by introducing them to the use and management of the Indonesian currency, the rupiah. The academic approach involved activities such as counting, basic buying and selling simulations, saving practices, and creative coloring tasks. Meanwhile, the non-academic approach included singing national and regional songs, storytelling of Indonesian folklore, and interactive games designed to maintain focus and engagement. The results showed a notable improvement in the children’s understanding of the rupiah and basic financial management, as well as increased interest in Indonesian culture and identity. The program’s strength lies in its contextual and enjoyable methods, although time limitations and facilitator dependency remain challenges. Future development is suggested through the integration of digital media and community involvement to support independent and sustainable learning.